2019
DOI: 10.1002/jmv.25602
|View full text |Cite
|
Sign up to set email alerts
|

Ribavirin induces hepatitis C virus genome mutations in chronic hepatitis patients who failed to respond to prior daclatasvir plus asunaprevir therapy

Abstract: Ribavirin (RBV) induces nucleotide (nt) substitutions in hepatitis C virus (HCV) genome nonstructural (NS) regions. Although emergence of drug resistance‐associated variants is associated with direct‐acting antiviral treatment failure, the effect of RBV on genome substitutions in such patients is unknown. Genotype 1b HCV subgenomic replicon cells were treated with RBV for 120 hours. Six patients with chronic genotype 1b with HCV‐infected patients who failed to respond to prior daclatasvir plus asunaprevir (DCV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The higher frequency of transition mutations compared to transversion mutations may be explained by viral polymerase fidelity. The same mutation patterns among in vitro biochemical analysis in HCV replicon cells and HCV-infected patients 20 , 22 , 24 suggests that the RdRp fidelity of HCV NS5B is a major factor in establishing the mutational spectrums of HCV RNA. Moreover, the higher frequency of the A>G and U>C than G>A and C>U transition substitutions are also thought to arise from the fidelity of HCV NS5B.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The higher frequency of transition mutations compared to transversion mutations may be explained by viral polymerase fidelity. The same mutation patterns among in vitro biochemical analysis in HCV replicon cells and HCV-infected patients 20 , 22 , 24 suggests that the RdRp fidelity of HCV NS5B is a major factor in establishing the mutational spectrums of HCV RNA. Moreover, the higher frequency of the A>G and U>C than G>A and C>U transition substitutions are also thought to arise from the fidelity of HCV NS5B.…”
Section: Discussionmentioning
confidence: 88%
“…C>U transition was the most frequent substitution among transitions). Previous reports have demonstrated that ribavirin induces C>U and G>A substitutions in HCV genome 24 , 26 , 27 . Therefore, the alterative mutation pattern during interferon-based therapy may be caused by the administration of ribavirin.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Based on differences in nucleotide sequences, HCV is divided into 8 genotypes with different geographical distribution, influencing disease progression and treatment response. [2] The most common genotype (GT) is GT1, which accounts for more than half of all HCV-infected patients worldwide, another common genotypes are GT3 and GT4. [3] Failure to provide antiviral treatment timely and effectively will lead to HCV progression, even leading to the most serious complications, including cirrhosis, liver function damage, hepatocellular carcinoma, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Based on differences in nucleotide sequences, HCV is divided into 8 genotypes with different geographical distribution, influencing disease progression and treatment response. [ 2 ] The most common genotype (GT) is GT1, which accounts for more than half of all HCV-infected patients worldwide, another common genotypes are GT3 and GT4. [ 3 ]…”
Section: Introductionmentioning
confidence: 99%